Mitochondrial Genome Characteristics and Comparative Genomic Analysis of Spartina alterniflora - Hong Zhu; Chunlei Yue; Hepeng Li (Current Issues in Molecular Biology, 2025)
The mitochondrial genome of Spartina alterniflora, an invasive species with significant ecological and economic impacts, was analyzed to provide a theoretical basis for understanding its phylogenetic relationships and molecular biology. Mitochondrial genome sequences of S. alterniflora and 23 related species from NCBI were utilized for bioinformatics and comparative genomic analyses. A sliding window analysis identified three genes (rps2, atp9, and nad6) as potential DNA barcodes for species identification. Intracellular gene transfer (IGT) events between mitochondrial and chloroplast genome were detected, highlighting the dynamic nature of genomic evolution. A selective pressure analysis revealed that most protein-coding genes (PCGs) underwent purifying selection (Ka/Ks < 1), while the nad2 and ccmB genes showed signs of positive selection pressure (Ka/Ks > 1), indicating their role in adaptation. A phylogenetic analysis demonstrated a close relationship between S. alterniflora and Eleusine indica, supported by a collinearity analysis, which suggests environmental convergence. This study provides novel insights into the structural and evolutionary characteristics of the S. alterniflora mitochondrial genome, offering valuable genomic resources for future research on invasive species management and evolutionary biology.